Предмет: Алгебра,
автор: arsik1ox
решить уравнение,Подробно
Приложения:

Ответы
Автор ответа:
2
Правильний розв‘язок на фото)))
Приложения:

Автор ответа:
2
(2х^2 + 11х - 76)/(х^2 - 16) = 3 | * х^2 - 16
2х^2 + 11х - 76 = 3(х^2 - 16)
2х^2 + 11х - 76 = 3х^2 - 48
2х^2 + 11х - 76 - 3х^2 + 48 = 0
-х^2 + 11х - 28 = 0
D = b^2 - 4ac
D = 11^2 - 4 × (-1) × (-28) = 121 - 112 = 9
x = (-b ± √D)/2a
x = (-11 ± √9)/(-2) = (- 11 ± 3)/(-2) = 7; 4
4 отсеивание, так как тогда в знаменателе будет 0, а делить на 0 нельзя
Похожие вопросы
Предмет: Физика,
автор: ZWER0BOY
Предмет: Математика,
автор: vadimka420
Предмет: Химия,
автор: informationcpab
Предмет: Математика,
автор: ХайЭтоИвангай
Предмет: Химия,
автор: АлисаРиммер